ASSESSMENT OF KAOLIN DEPOSITS IN OGBADIBO AND OTUKPO LOCAL GOVERNMENT AREAS OF BENUE STATE USING NUCLEAR ANALYTICAL TECHNIQUE AND THEIR POSSIBLE APPLICATIONS IN INDUSTRY - Obonyilo, Ojegburu Shadrach; Agu, Matthew Nnamdi (FUDMA Journal of Sciences, 2026)
An assessment of the kaolin deposits in Ogbadibo and Otukpo Local Government Areas of Benue State, Nigeria, was carried out using X-Ray Fluorescence Spectrometry–Fundamental Parameter (XRF-FP). This was to determine the elemental compositions and physicochemical characteristics and geological formation differences as well as their industrial suitability. Kaolin is versatile industrial clay which has found important applications in paper coating, ceramics, paints and plastics due to its high opacity, soft texture, and chemical inertness. Thus, knowledge of their composition as well as the purity and impurity concentrations would be of economic advantage to local industries which oftentimes import their raw materials. In addition, it will increase the economic base of the state. In this work four (4) kaolin samples were collected, oven-dried at 105°C, pulverized, homogenised, and pelletized with 15% boric acid binder and analysed at the National Steel Raw Materials Exploration Agency (NSRMEA), Kaduna. The results obtained revealed that silicon oxide (SiO₂) and aluminium oxide (Al₂O₃) were the dominant oxides in both locations, confirming kaolinite (Al₂Si₂O₅(OH)₄) as the major mineral phase.
Keywords: Aluminosilicate; Assessment; Lower Benue Trough; Feldspars; Kaolinite; Quartz; Stratigraphy